KNOWLEDGE AND PRACTICES REGARDING VITAMIN D DEFICIENCY AMONG WOMEN ATTENDING IMAM HUSSEIN MEDICAL CITY IN KARBALA 2018 - AL-GHRAIBAWI, SARAH JAFAR; AL-GHABBAN, SAAD IBRAHIM; AL-ZUBAIDY, RIYADH DHEYHOOD (International Journal of Current Pharmaceutical Research, 2019)
Objective: Vitamin D deficiency is a global health problem. It is significantly associated with skeletal and non-skeletal problems. Prevention can be maintained mainly by effective sun exposure or supplementation and to lesser extent by dietary intake. To determine the magnitude of knowledge and practice of women towards vitamin D deficiency. Methods: A cross-sectional study, purposive sample of 442 women were approached who attended consultants’ clinics of Imam Hussein Medical City in Karbala. Data collection done between March 2 and June 30, 2018 through direct interviews using a special questionnaire prepared for the purpose of the study. Results: Less than half (45.2%) of the women had heard about vitamin D; their source of information was from relatives and friends then from health care provider. The mean score for the participants’ knowledge about VDD was 4.25 out of 9.0 (47%). It has a significant association with higher educational levels and urban residence. There is no significant difference regarding age, marital status or occupation. The mean score for the participants’ practice about vitamin D deficiency was 2.53 out of 5 (50.71%). There is no influence of practice score by socio-demographic factors. Conclusion: Overall knowledge towards vitamin D deficiency was suboptimal. Improving practices towards VD is directly related to increase knowledge about it that indicates the need to increase public awareness about the problem, encourage appropriate way of sun exposure, consumption of vitamin D rich food and taking supplementation when sun exposure is difficult.